161k views
5 votes
X^1 - x^-1 + x^0 for x =2

2 Answers

1 vote

Answer:

For x = 2 the value of the expression is 2.5

Explanation:

the given expression is
x^(1) - x^(-1) + x^(0) = x -((1)/(x)) + 1

Simplifying further
(x^(2)-1 )/(x) + 1

Now if we put the value of x = 2 in the simplified form of the expression we get


(x^(2) - 1)/(2) + 1 =
(4-1)/(2) + 1 = (3)/(2) + 1 = 1.5 + 1 = 2.5

User Smbd Uknow
by
5.5k points
3 votes

Answer:

2 1/2

Explanation:

X^1 - x^-1 + x^0

Let x=2

2^1 - 2^(-1) +2^0

We know that negative exponents put the number in the denominator and anything to the zero power is 1

2 - 1/2 +1

Rewriting

2+1-1/2

3-1/2

2 1/2

User Jakub H
by
6.4k points